Introduced species in the Pantanal: implications for conservation - CJR. Alho; S. Mamede; K. Bitencourt; M. Benites (Brazilian Journal of Biology)
Land use and human occupation within the natural habitats of the Pantanal have facilitated introduction of invasive species of plants and animals, including domestic species. Exotic species threaten regional biodiversity because they modify ecological community structure, alter natural habitats and affect local biodiversity. An international organisation, the International Union for Conservation of Nature (IUCN), and the Brazilian government, identify invasive species as the third most important threat to biodiversity, following habitat loss and direct effect on species. In addition, exotic species carry pathogens or may function as vectors or reservoirs for diseases that affect regional biota.